1982
DOI: 10.1002/bip.360210504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactants on the conformation of β‐lactoglobulin B using circular dichroism

Abstract: SynopsisThe effect of several surfactants on the secondary structure of bovine 0-lactoglobulin B was determined from the circular dichroism spectra. The spectra were measured a t several concentrations of surfactant ranging from 1 mg/mL to the critical micelle concentration. The surfactants studied were sodium dodecyl, decyl, and octyl sulfate, sodium dodecyl sarcosinate, dodecyltrimethylammonium bromide. The data were analyzed using the method of Chen et al. [Biochemistry (1974) 13,3350-33591 to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our previous circular dichroism studies (10) have shown that the addition of both sodium octyl and decyl sulfate abruptly increases the amount of a-helical and 8-structure of 8-lactoglobulin at the expense of the unordered form in aqueous solution at 22 + 1 °C. Therefore, studies were performed under similar conditions (10) with aqueous solutions of 8-lactoglobulin AB using the electrodes to determine if the binding behavior paralleled the conformational changes. The results obtained resembled the titration curves shown in Figure 4 for the titration of PVP.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Our previous circular dichroism studies (10) have shown that the addition of both sodium octyl and decyl sulfate abruptly increases the amount of a-helical and 8-structure of 8-lactoglobulin at the expense of the unordered form in aqueous solution at 22 + 1 °C. Therefore, studies were performed under similar conditions (10) with aqueous solutions of 8-lactoglobulin AB using the electrodes to determine if the binding behavior paralleled the conformational changes. The results obtained resembled the titration curves shown in Figure 4 for the titration of PVP.…”
Section: Methodsmentioning
confidence: 94%
“…1978, 253, 4971-4979. (10) Dryhurst, G. "Electrochemistry of Biological Molecules"; Academic Press: New York, 1977; Chapter 7.…”
Section: Literature Citedmentioning
confidence: 99%
“…Bovine ␤-lactoglobulin (␤-lg) is the major protein in whey (Wong et al, 1996). ␤-Lg has been highly characterized over recent years in all aspects of its behaviour from structural and biochemical properties (Damon & Kresheck, 1982;Papiz et al, 1986;Huang et al, 1994;Wong et al, 1996;Manderson et al, 1998;Renard et al, 1998) to functional properties such as lipid binding (Jones & Wilkinson, 1976;Damon & Kresheck, 1982;Coke et al, 1990;Clark et al, 1992), adsorption (Waniska & Kinsella, 1985;Luey et al, 1991) foaming (Coke et al, 1990), gelation (Foegeding et al, 1992) and emulsification (Shimizu et al, 1985;Das & Kinsella, 1989;Cornec et al, 1998). It has two main genetic variants; ␤-lg A (mol.…”
Section: Introductionmentioning
confidence: 99%
“…ES of emulsions increased with increasing protein concentration. SDS can change the conformation of proteins (8,10,24) and stabilize the helix of proteins by forming a hydrophobic shield around peptide bonds (12). It was thought that S 0 may be a static factor and flexibility a dynamic factor in the surface properties of proteins (15).…”
Section: Resultsmentioning
confidence: 99%
“…Protein ingredients in cosmetics can enhance those detergent functions and protect skin from the undesirable effects of detergents. Detergents can modify protein conformation and increase protein dispersability and surface hydrophobicity (8)(9)(10)(11). Teglia et al (6) demonstrated the cosmetic properties of protein hydrolysates-sodium lauryl sulfate complex (6).…”
mentioning
confidence: 98%